1981
DOI: 10.1111/j.1600-0765.1981.tb00947.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclosporin A on periodontal disease in rats monoassociated with Actinomyces viscosus Ny 1

Abstract: The T‐cell triggered effector systems have been emphasized as the most important agents mediating periodontal disease in recent years. It was therefore tempting to investigate whether T‐cell suppression with cyclosporin A (CS‐A) had an effect on the establishment and progression of the disease in rats monoassociated with Actinomyces viscosus Ny 1. The experiment was carried out with two treatments (16 rats each) in two isolators. In one of the isolators CS‐A was added to the high sucrose diet 2000 aiming at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The positive effect of immunization is in agreement with previous investigations reporting reduced periodontal bone loss in germ-free rats immunized against Streptococcus mutans (9), Aetinoinyces naeshtndii (9), and Eikenella corrodens (2) prior to tnonoinfection with the homologous organism. Other investigators have found increased bone loss in similar studies after immunization against Actinomyees viscosus (5,19,20) and Aetinobaeillus actinomycetemeomitans (51). This discrepancy may be explained by differences in imtnunization route and cotnposition of antigen preparation.…”
mentioning
confidence: 89%
“…The positive effect of immunization is in agreement with previous investigations reporting reduced periodontal bone loss in germ-free rats immunized against Streptococcus mutans (9), Aetinoinyces naeshtndii (9), and Eikenella corrodens (2) prior to tnonoinfection with the homologous organism. Other investigators have found increased bone loss in similar studies after immunization against Actinomyees viscosus (5,19,20) and Aetinobaeillus actinomycetemeomitans (51). This discrepancy may be explained by differences in imtnunization route and cotnposition of antigen preparation.…”
mentioning
confidence: 89%
“…42 While few studies have been performed that detail the humoral immune response to Gram-positive microorganisms in an animal model of periodontitis, a study by Crawford et al 43 showed that the induction of serum and salivary antibody appeared to provide a measure of protection from bone loss induced by infection of germfree rats with either S. mutans or A. naeslundii. Guggenheim and co-workers 44 examined the ability of a T-lymphocyte inhibiting agent (Cyclosporine A) to effect both immune responses and disease in rats challenged with A. viscosus. The results showed a dramatic decrease in serum agglutinins to A. viscosus in the CyA-treated rats.…”
Section: Antibody To Gram-positive Microorganismsmentioning
confidence: 99%
“…For example, dinitrochlorobenzene challenge could induce an early gingival lesion, resembling a delayed hypersensitivity reaction in monkeys and rats. 28 The lesions in rats could be passively transferred with sensitized cells and not with serum.3 Dinitrochlorobenzene-induced disease in sensitized dogs could be suppressed by anti-thymocyte serum. 29 In mice, only animals demonstrating a cellmediated immune (CMI) response to the superinfecting micro-organism developed bone loss.30 Analysis of our data indicates that a single antigen administered to animals otherwise germ-free and antigen-free can result in enhanced periodontal bone loss, as can pre-sensitization prior to antigen administration.4'22 Evidence implicating CMI in periodontal disease involved the demonstration that lymphokines (produced after oral antigen stimulation) gave rise to some symptoms of periodontal disease.…”
mentioning
confidence: 98%